Low-sodium high-magnesium continuous casting crystallizer casting powder for low-carbon cold-rolled electroplated tin steel plate

By using high MgO to replace Na2O and Li2O protective slag in cold-rolled electroplated tin steel plate production, combined with appropriate amounts of Al2O3 and F-, the problems of high production costs and steel defects are solved, and the high quality of low-carbon tin plates are achieved Surface quality and economic benefits.

CN119216540AInactive Publication Date: 2024-12-31SHANGHAI MEISHAN IRON & STEEL CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310795500.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-30
Publication Date
2024-12-31
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the prior art, the production cost of protective slag in the cold-rolled electroplated tin steel plate is high and is prone to cause steel defects, especially the "white spot" defects, which is difficult to meet the high surface quality requirements of low-carbon cold-rolled electroplated tin steel plates.

Method used

By scientifically configuring the components of the protective slag, using high MgO instead of Na2O and Li2O, controlling the Al2O3 content, and coordinating with F- and other components, ensuring that the protective slag has appropriate viscosity and melting point, reducing the Na2O content to avoid 'white spots' defects. Li2O is not included to reduce production costs.

Benefits of technology

It effectively reduces the hot-rolled defect rate of low-carbon tin-plated steel, from 1.29% to below 0.9%, reduces the production cost of protective slag, improves the surface quality, and avoids the occurrence of 'white spots' defects.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses low-sodium high-magnesium casting powder for a continuous casting crystallizer for a low-carbon cold-rolled electroplated tin steel plate, and mainly solves the technical problems that the production cost of the casting powder is high in the process of producing a low-carbon cold-rolled electroplated tin steel casting blank by using an existing slab continuous casting machine, and the casting powder for the continuous casting crystallizer is easy to roll to cause steel defects. According to the technical scheme, the low-sodium high-magnesium continuous casting crystallizer casting powder for the low-carbon cold-rolled electroplated tin steel plate comprises the following components in percentage by mass: 34.5%-40.5% of SiO2, 30.2%-36.2% of CaO3, 0.5%-2.0% of Al2O3, 6.2%-8.0% of MgO, less than or equal to 2.0% of Na2O + K2O, 7.5%-9.5% of F, less than or equal to 5.0% of CF and the balance of inevitable impurities. And the binary alkalinity of the casting powder ranges from 0.83 to 0.95. By the adoption of the casting powder, the hot rolling defect degradation rate of the low-carbon cold-rolled tinned steel is reduced to 0.9% or below.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a protective slag for a continuous casting crystallizer used in a slab continuous casting machine for casting molten steel, and in particular to a low-sodium and high-magnesium continuous casting crystallizer protective slag for low-carbon cold-rolled electro-tinned steel plates, belonging to the technical field of metallurgical auxiliary materials for steelmaking. Background Art

[0002] Cold-rolled electroplated tin steel sheet is a cold-rolled low-carbon thin steel sheet plated with pure tin on both sides. Its carbon content generally ranges from 0.01% to 0.13%. It has the characteristics of both steel and tin, combining the strength of steel with the corrosion resistance and weldability of tin. Due to its excellent barrier properties and mechanical properties, it is widely used in food packaging fields such as beverages and canned foods, and has high process requirements.

[0003] With the continuous reduction in the thickness of cold-rolled tinplate, the control of inclusions in steel has gradually become a key technology for the production of high-quality tinplate. After rolling, the surface of the steel plate is prone to "white spots" and slag inclusions, which is one of the common surface defects of tinplate. After analysis, it was found that the slag inclusion composition of the "white spots" is basically the same as that of the protective slag. This type of defect is caused by the inclusion of protective slag. The "white spots" defect on the surface of cold-rolled tinplate is mainly caused by the Na in the mold protective slag. + NaOH is enriched on the surface of the continuous casting billet, and NaOH has a strong corrosive effect on the tin layer of the cold-rolled electroplated tin steel sheet, causing the "white spot" defect of the cold-rolled electroplated tin steel sheet.

[0004] In traditional mold slag, Na2O, Li2O, F - It is an ideal flux, and the ratio is generally 2%-10%. They can reduce the melting point and viscosity of the protective slag and control the phase of the crystallization. In order to reduce the "white spot" defect, it is necessary to control the amount of Na2O added to the protective slag. However, as the Na2O content decreases, the melting point of the protective slag increases rapidly. At present, the protective slag for continuous casting crystallizers of cold-rolled electroplated tin steel plates developed and produced at home and abroad mostly uses Li2O instead of Na2O as a flux. However, with the development of the electric vehicle industry, the price of lithium carbonate has risen, causing the production cost of the protective slag to rise. For this reason, it is necessary to find some other fluxes to replace Na2O to achieve the metallurgical function of the protective slag, while effectively reducing costs.

[0005] Chinese patent CN1411931A discloses a CSP thin slab continuous casting crystallizer protective slag, the MgO content of the protective slag of the invention is 3.0%-6.0%, which mainly solves the problem of poor lubrication and uneven heat transfer caused by reduced slag consumption in the thin slab continuous casting process of the prior art. In addition to a certain amount of MgO, the patent also adds 3.0%-6.0% BaO and 1.0%-2.5% Li2O as flux.

[0006] Chinese patent CN1824429A discloses a high-speed slab continuous casting low-carbon steel mold protection slag, which mainly solves the existing high-speed slab continuous casting low-carbon steel technology caused by bonding leakage, slag inclusion on the surface of the casting and slag quality problems. In addition to a certain amount of MgO, the patent also adds 1.0%-1.5% Li2O, 2.0%-3.0% MnO and Na2O, F - And other fluxes. And the protective slag has the characteristics of low melting point and low viscosity, which is suitable for continuous casting to produce high-speed low-carbon steel, but not suitable for conventional speed cold-rolled tin-plated steel sheets.

[0007] Although a certain amount of MgO or BaO is added as flux in the prior art, the addition of Li2O cannot be completely avoided, and the purpose of reducing costs cannot be achieved. At the same time, the physical properties of the protective slag cannot meet the production requirements of cold-rolled tin-plated steel sheets. Summary of the invention

[0008] The purpose of the present invention is to provide a low-sodium and high-magnesium continuous casting crystallizer protective slag for low-carbon cold-rolled tin-plated steel plates, which mainly solves the technical problems of high production cost of protective slag in the process of producing low-carbon cold-rolled tin-plated steel ingots by existing slab continuous casting machines and easy slag rolling and steel defects caused by protective slag used in continuous casting crystallizers.

[0009] The technical idea of ​​the present invention is to scientifically configure the components of the protective slag, adopt a high MgO design, reduce the amount of flux such as Na2O and Li2O in the protective slag, and control the Al2O3 content in the protective slag to prevent the formation of high-melting-point magnesium-aluminum spinel. - The coordination of other components ensures that the protective slag has a suitable viscosity and melting point, and ensures that the physical and chemical properties of the protective slag can meet the requirements of high surface quality of cast low-carbon tinplate. The lower Na2O content can effectively avoid the generation of "white spot" defects in tinplate. At the same time, the protective slag does not contain Li2O, which has a lower production cost. Through the implementation of the patent of this invention, the hot rolling defect degradation rate of low-carbon tinplate steel can be reduced from the current 1.29% to below 0.9%.

[0010] The technical scheme adopted by the present invention is a low-sodium and high-magnesium continuous casting crystallizer protection slag for low-carbon cold-rolled electroplated tin steel sheet, the mass percentage of the components of which are: SiO2 34.5%-40.5%, CaO 30.2%-36.2%, Al2O3 0.5%-2.0%, MgO

[0011] 6.2%-8.0%, Na2O+K2O≤2.0%, F - 7.5%-9.5%, C F ≤5.0%, the remainder being inevitable impurities; the binary basicity (CaO / SiO2) of the protective slag is 0.83-0.95.

[0012] The physical properties of the protective slag are as follows: the melting temperature (hemisphere point temperature) of the protective slag is 1230-1290° C., and the viscosity of the protective slag at 1300° C. is 0.16-0.28 Pa·S.

[0013] As a further preference, the viscosity of the protective slag at 1300° C. is 0.20-0.24 Pa·S.

[0014] As a further preference, the mass percentage of Na2O in the protective slag is ≤1.0%≤1.0%.

[0015] As a further preference, the mass percentage of carbon in the low-carbon cold-rolled tin-plated steel sheet is 0.02%-0.09%.

[0016] The reasons why the chemical composition of the low-sodium and high-magnesium continuous casting mold powder for low-carbon cold-rolled tin-plated steel sheets according to the present invention is limited to the above range are as follows:

[0017] Basicity: The binary basicity of the mold slag is the mass of CaO / the mass of SiO2 in the mold slag. Since low-carbon tinplate steel is not sensitive to surface longitudinal cracks, the main function of the mold slag is to provide sufficient lubrication. Therefore, the mold slag is required to be glassy. As the basicity increases, the crystallization temperature of the mold slag will increase. Considering comprehensively, the basicity of this mold slag is set to 0.83-0.95.

[0018] MgO: MgO is a common flux for continuous casting mold slag, which has the functions of lowering the melting temperature and improving the rheological properties of the mold slag. The continuous casting mold mold slag is also the slag system with the widest range of MgO components. However, in the traditional CaO-SiO2 mold slag, CaO is usually introduced as an impurity or replaced in small amounts to adjust the basicity. The MgO content is 0-5%. MgO is an oxide of alkaline earth metals and has the function of providing O to the slag. 2- The capacity of ions, O 2- The ability of ions to promote the disintegration of silicon-oxygen polymers is enhanced, making the composite anion group smaller, which can promote the decrease of slag viscosity. Generally speaking, when the MgO content is increased in the low basicity range, the viscosity decreases significantly. With the increase of MgO content, the crystallization temperature of the protective slag decreases significantly. When the MgO content increases from 7% to 9%, the crystallization temperature drops by 226°C and the crystallization rate decreases by 12.5%. Taking all factors into consideration, the MgO content in this protective slag is set to 6.2%-8.0%.

[0019] Al2O3: In order to ensure the uniformity of the ingot shell of the low-carbon tinplate casting, the mold protection slag should have good lubrication and inclusion adsorption capabilities. In order to improve the ability of the protection slag to absorb Al2O3, the initial Al2O3 content in the slag must be reduced. At the same time, the protection slag is designed with high MgO. The presence of Al2O3 has the greatest impact on the performance of MgO properties. Too high Al2O3 is easy to form magnesium-aluminum spinel with a high melting point, which destroys the uniformity of the slag, thereby causing the apparent viscosity of the protection slag to increase, and the performance of the protection slag is deteriorated. Considering the ability of the low-carbon tinplate protection slag to absorb Al2O3 inclusions and prevent the formation of high-melting-point magnesium-aluminum spinel, the Al2O3 in this protection slag is set to 0.5%-2%.

[0020] Na2O, K2O: Na2O and K2O are both good fluxing agents, which can significantly reduce the melting temperature of the protective slag, improve the fluidity of the slag, improve the lubrication effect and absorption capacity of the protective slag, and effectively prevent the occurrence of bonding and leakage. However, Na2O is an alkali metal, and the Na-O bond energy is much weaker than the Si-O bond energy. As the Na2O content increases, its depolymerization effect is enhanced, the polymer size becomes smaller, and the inter-ionic potential decreases, thereby reducing the surface tension of the melt and making it easy for the crystallizer to roll slag. Na2O rolled into the ingot is likely to cause the "white spot" defect of the tinplate. The Na2O content in the tinplate steel with high surface quality requirements should be as low as possible. The sum of Na2O and K2O in this protective slag is set to ≤2.0%, and the effect is better when Na2O ≤1.0%.

[0021] F - : F - It is also one of the commonly used fluxes for protective slag. - The increase of the addition amount will increase the crystallization rate of the mold slag. - When the addition amount exceeds 10.22%, a large amount of gunite is generated, and the crystallization rate of the protective slag film is as high as about 90%, which is easy to deteriorate lubrication and cause bonding and leakage accidents. For low-carbon steels with high lubrication requirements, when using F - When used as flux, the F content in the protective slag should be controlled. - Less than 10.22%. - Set to 7.5%-9.5%.

[0022] C F :In the continuous casting process, the carbon in the mold slag plays the role of skeleton and regulating the melting characteristics of the mold slag. As the amount of carbon material increases, the melting rate decreases. The melting rate is an important characteristic of the mold slag, and an appropriate value should be maintained during production. If the melting is too fast, the powder slag layer of the mold slag is not easy to maintain, and the insulation effect of the mold slag is poor; if the melting is too slow, the liquid slag layer is too thin, the absorption capacity of inclusions is poor, and the surface quality of the ingot is deteriorated. F ≤5.0%.

[0023] The raw materials of the present invention include cement clinker, wollastonite, quartz sand, fluorite, magnesia, carbon black and graphite; the weight percentages of the raw material components of the protective slag of the present invention are: 10%-13% of cement clinker, 36%-41% of wollastonite, 14%-17% of quartz sand, 17%-21% of fluorite, 5%-7% of magnesia, 2%-3% of carbon black, 2%-4% of graphite, and the sum of the weight percentages of the raw material components of the protective slag is 100%.

[0024] The raw materials for the protective slag of the present invention are all industrial raw materials, and the weight percentages of the components of the raw materials are as follows:

[0025] Cement clinker: CaO 62%~64%, SiO220%~23%;

[0026] Wollastonite: CaO 40%~44%, SiO250%~55%, Al2O3<1.5%, MgO 1%-3%;

[0027] Quartz sand: SiO2 ≥ 96%;

[0028] Fluorite: CaF2>97%;

[0029] Magnesia: MgO ≥ 95%;

[0030] Carbon black: C>98.5%;

[0031] Graphite:>95%;

[0032] The method for preparing the low-sodium and high-magnesium continuous casting mold protection slag for the low-carbon cold-rolled tin-plated steel sheet comprises the following steps:

[0033] 1) Weigh cement clinker, wollastonite, quartz sand, fluorite and magnesia sand according to the proportion, crush, stir and pre-melt in sequence to obtain pre-melted material, grind the pre-melted material to control the particle size of the pre-melted material to <200 mesh;

[0034] 2) weighing carbon black and graphite according to the ratio, grinding them into powder, and mixing them with the pre-melted material described in step 1) to obtain a mixed powder;

[0035] 3) Put the mixed powder, water and binder into a fine grinder according to the proportion and grind them into slurry. The grinding time is 50 to 80 minutes;

[0036] 4) The slurry obtained in step 3) is spray-dried and granulated to obtain a finished protective slag.

[0037] Compared with the prior art, the present invention has the following positive effects: 1. The MgO content in the protective slag of the present invention is 6.2%-8.0%, and MgO is used to replace fluxes such as Na2O and Li2O, and the Al2O3 content in the protective slag is reasonably controlled to be 0.5%-2%.- 1. The coordination of other components ensures that the protective slag has a suitable viscosity and melting point, eliminates the adverse effects of MgO and Al2O3 generating high-melting-point magnesium-aluminum spinel, and satisfies the smooth continuous casting of low-carbon cold-rolled tin-plated steel slabs. 2. The Na2O content in the protective slag of the present invention is ≤1.0%. Lower Na2O can increase the surface tension of the protective slag and reduce the risk of slag rolling. At the same time, it can reduce or avoid defects such as "white spots" of low-carbon cold-rolled tin-plated steel plates caused by Na2O in the protective slag. 3. The protective slag of the present invention does not contain Li2O. The cost of lithium carbonate is 100 times that of magnesia. Using MgO instead of Li2O to protect the slag production cost is greatly reduced, and good economic benefits can be achieved. 4. The use of the protective slag of the present invention reduces the hot rolling defect degradation rate in the process of casting low-carbon cold-rolled tin-plated steel slabs by the slab continuous caster from the current 1.29% to below 0.9%. DETAILED DESCRIPTION

[0038] The present invention is further described below in conjunction with Examples 1 to 5, as shown in Table 1.

[0039] Table 1 shows the composition of the protective slag according to the embodiment of the present invention (by weight percentage), and the remainder is inevitable impurities.

[0040] Table 1 Compositions of the protective slag in the embodiments of the present invention, unit: %.

[0041] Components CaO <![CDATA[SiO2]]> <![CDATA[Al2O3]]> MgO <![CDATA[Na2O+K2O]]> <![CDATA[F - ]]> <![CDATA[C F ]]> The present invention 30.2-36.2 34.5-40.5 0.5-2.0 6.2-8.0 ≤2.0 7.5-9.5 ≤5 Example 1 35.4 37.9 1.3 7.4 1.3 8.6 2.5 Example 2 35.2 39.4 1.2 7.8 1.6 9.4 2.6 Example 3 33.9 38.3 1.1 6.8 1.8 7.7 2.5 Example 4 30.5 36.7 0.7 6.7 1.4 7.6 2.1 Example 5 33.1 34.9 0.8 7.7 1.5 8.1 2.6

[0042] In Examples 1-5 of the present invention, the mass percentages of Na2O in the protective slag are 0.5%, 0.7%, 0.7%, 0.5% and 0.6% respectively; the mass percentages of K2O are 0.8%, 0.9%, 1.1%, 0.9% and 0.9% respectively; the binary basicity values ​​of the protective slag are 0.93, 0.89, 0.88, 0.83 and 0.95 respectively; the melting temperatures (hemisphere point temperatures) are 1276°C, 1257°C, 1264°C, 1287°C and 1261°C respectively; the viscosities at 1300°C are 0.20Pa·s, 0.21Pa·s, 0.24Pa·s, 0.20Pa·s and 0.22Pa·s respectively.

[0043] The protective slag in the embodiment of the present invention is used for the production of low-carbon tinplate steel, and the steel grade MRT-4CA is produced; during the continuous casting process, the casting section is 230mm*750~1350mm, and the pulling speed is 0.9m / min~1.6m / min.

[0044] Example 1, the average slag consumption of protective slag is 0.51Kg / ton of steel, and the thickness of the liquid slag layer is 11-14mm. The test results show that the crystallizer protective slag has good spreadability and less smoke. After adding the protective slag, the slag surface of the crystallizer is in good slagging condition, the three-layer structure of the protective slag melting is relatively stable, the protective slag does not agglomerate, the spreadability is normal, the air permeability is normal, and the slag strip control is normal. The crystallizer leakage prediction thermocouple temperature curve is generally normal. A total of 116 slabs were produced, and no leakage prediction occurred during the continuous casting process. The hot-rolled steel quality defect degradation rate was 0.61%.

[0045] Example 2, the average slag consumption of protective slag is 0.48Kg / ton of steel, and the thickness of the liquid slag layer is 10-15mm. The test results show that the crystallizer protective slag has good spreadability and less smoke. After adding the protective slag, the slag surface of the crystallizer is in good slagging condition, the three-layer structure of the protective slag melting is relatively stable, the protective slag does not agglomerate, the spreadability is normal, the air permeability is normal, and the slag strip control is normal. The crystallizer leakage prediction thermocouple temperature curve is generally normal. A total of 144 slabs were produced, and no leakage prediction occurred during the continuous casting process. The hot-rolled steel quality defect degradation rate was 0.34%.

[0046] Example 3, the average slag consumption of protective slag is 0.49Kg / ton of steel, and the thickness of the liquid slag layer is 10-15mm. The test results show that the crystallizer protective slag has good spreadability and less smoke. After adding the protective slag, the slag surface of the crystallizer is in good slagging condition, the three-layer structure of the protective slag melting is relatively stable, the protective slag does not agglomerate, the spreadability is normal, the air permeability is normal, and the slag strip control is normal. The crystallizer leakage prediction thermocouple temperature curve is generally normal. A total of 132 slabs were produced, and no leakage prediction occurred during the continuous casting process. The hot-rolled steel quality defect degradation rate was 0.75%.

[0047] Example 4, the average slag consumption of protective slag is 0.55Kg / ton of steel, and the thickness of the liquid slag layer is 11-15mm. The test results show that the crystallizer protective slag has good spreadability and less smoke. After adding the protective slag, the slag surface of the crystallizer is in good slagging condition, the three-layer structure of the protective slag melting is relatively stable, the protective slag does not agglomerate, the spreadability is normal, the air permeability is normal, and the slag strip control is normal. The crystallizer leakage prediction thermocouple temperature curve is generally normal. A total of 108 slabs were produced, and no leakage prediction occurred during the continuous casting process. The hot-rolled steel quality defect degradation rate was 0.72%.

[0048] Example 5, the average slag consumption of protective slag is 0.53Kg / ton of steel, and the thickness of the liquid slag layer is 11-14mm. The test results show that the crystallizer protective slag has good spreadability and less smoke. After adding the protective slag, the slag surface of the crystallizer is in good slagging condition, the three-layer structure of the protective slag melting is relatively stable, the protective slag does not agglomerate, the spreadability is normal, the air permeability is normal, and the slag strip control is normal. The crystallizer leakage prediction thermocouple temperature curve is generally normal. A total of 136 slabs were produced, and no leakage prediction occurred during the continuous casting process. The hot-rolled steel quality defect degradation rate was 0.69%.

[0049] In addition to the above embodiments, the present invention may also have other implementation modes. Any technical solution formed by equivalent replacement or equivalent transformation falls within the protection scope required by the present invention.

Claims

1. A low-sodium and high-magnesium continuous casting mold protection slag for low-carbon cold-rolled tin-plated steel sheets, characterized in that: The mass percentage of its components is: SiO234.5%-40.5%, CaO 30.2%-36.2%, Al2O30.5%-2.0%, MgO 6.2%-8.0%, Na2O+K2O≤2.0%, F - 7.5%-9.5%, C F ≤5.0%, the remainder being unavoidable impurities; the binary basicity of the protective slag is 0.83-0.95, the melting temperature of the protective slag is 1230-1290°C, and the viscosity of the protective slag at 1300°C is 0.16-0.28Pa·S; the mass percentage of carbon in the low-carbon cold-rolled tin-plated steel sheet is 0.02%-0.09%.

2. The low-sodium and high-magnesium continuous casting mold protection slag for low-carbon cold-rolled tin-plated steel sheets according to claim 1, characterized in that: The protective slag is prepared from industrial raw materials such as cement clinker, wollastonite, quartz sand, fluorite, magnesia, carbon black and graphite according to the ingredients of claim 1.

3. The low-sodium and high-magnesium continuous casting mold protection slag for low-carbon cold-rolled tin-plated steel sheets according to claim 1, characterized in that: The weight percentages of the raw material components of the protective slag are: 10%-13% cement clinker, 36%-41% wollastonite, 14%-17% quartz sand, 17%-21% fluorite, 5%-7% magnesia, 2%-3% carbon black, and 2%-4% graphite. The sum of the weight percentages of the raw material components of the protective slag is 100%.

4. The low-sodium and high-magnesium continuous casting mold protection slag for low-carbon cold-rolled tin-plated steel sheets according to claim 2 or 3, characterized in that: The purity of the protective slag raw materials is measured by mass percentage, cement clinker: CaO 62%-64%, SiO2 20%-23%; wollastonite: CaO 40%-44%, SiO2 50%-55%, Al2O3<1.5%, MgO 1%-3%; quartz sand: SiO2≥96%; fluorite: CaF2>97%; Magnesia: MgO≥95%; Carbon black: C>98.5%; Graphite: >95%.

5. The low-sodium and high-magnesium continuous casting mold protection slag for low-carbon cold-rolled tin-plated steel sheets according to claim 1, characterized in that: The viscosity of the protective slag at 1300° C. is 0.20-0.24 Pa·S.

6. A method for preparing the low-sodium and high-magnesium continuous casting mold protection slag for low-carbon cold-rolled tin-plated steel sheets as claimed in claim 1, characterized in that: The following steps are involved: 1) Weigh cement clinker, wollastonite, quartz sand, fluorite and magnesia sand according to the proportion, crush, stir and pre-melt in sequence to obtain pre-melted material, grind the pre-melted material to control the particle size of the pre-melted material to <200 mesh; 2) weighing carbon black and graphite according to the ratio, grinding them into powder, and mixing them with the pre-melted material described in step 1) to obtain a mixed powder; 3) Put the mixed powder, water and binder into a fine grinder according to the proportion and grind them into slurry. The grinding time is 50 to 80 minutes; 4) The slurry obtained in step 3) is spray-dried and granulated to obtain a finished protective slag.

Citation Information

Patent Citations

  • Crystallizer casting powder

    CN103372637A

  • Protecting slag for car plate steel continuous casting crystallizer and preparation method and application thereof

    CN109732048A

  • Continuous casting crystallizer casting powder for casting medium carbon steel

    CN114247860A

  • Fluoride-free continuous casting mold flux for ultralow carbon steel

    WO2014114123A1